Sediment Management Strategies for Hydropower Reservoirs in Active Agricultural Area - A.Z, Abdul Razad; N.A, Abbas; Sidek. L, Mohd; J.L, Alexander; K, Jung (International Journal of Engineering and Technology, 2018)
Ringlet, Jor and Mahang reservoirs are part of Cameron Highlands – Batang Padang Hydroelectric Scheme. Conversion of forest to agricultural and urban area within the catchment has caused Ringlet Reservoir to suffer severe sedimentation problem and waste dumping. This has caused operational difficulties to the hydropower operator. Based on estimation, sediment inflow into Ringlet Reservoir has increased multiple folds from 25,000 m3/year in 1960s up to between 120,000 m3/year to 200,000 m3/year in 2010. This reduces the total storage capacity of Ringlet Reservoir to almost 50% of its original design value, and subsequently affects Jor and Mahang Reservoirs. Bertam Intake is often choked by the sediment built up within the area, thus limiting the running hours of the plant to generate electricity. Without sediment management strategies, the incoming sediment load into Ringlet Reservoir would increase tremendously and can cause the hydropower scheme to cease operation faster that its design life expectancy. Various mitigation strategies have been implemented such as dredging, construction of check dams and settling basins and flushing from the bottom outlet, resulting to an increase in storage. Despite these efforts which focus within the reservoir, the best solution is by control the sediment and waste at source, through the concept of an integrated catchment management. This requires concerted effort from the local authorities and public to ensure successful implementation. This paper outlines the methods, analyses and results of various mitigation strategies.